2017
DOI: 10.1177/0954411916683222
|View full text |Cite
|
Sign up to set email alerts
|

Computational modeling of long-term effects of prophylactic vertebroplasty on bone adaptation

Abstract: Cement augmentation in vertebrae (vertebroplasty) is usually used to restore mechanical strength after spinal fracture but could also be used as a prophylactic treatment. So far, the mechanical competence has been determined immediately post-treatment, without considering long-term effects of bone adaptation. In this work, we investigated such long-term effects of vertebroplasty on the stiffness of the augmented bone by means of computational simulation of bone adaptation. Using micro-finite element analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Case E aimed at investigating an extreme case where the bone tissue was so deteriorated that it could be neglected. The long-term behaviour of the bone present in the augmented region is unclear, 24 so results obtained with method E are a representation of one of the worst possible cases. It is also worth noticing the similarity between approaches E (bone tissue is neglected) and B (pure porous PMMA).…”
Section: Figure 8 Distribution Of Bone Cement Volume (Relative Frequementioning
confidence: 99%
See 2 more Smart Citations
“…Case E aimed at investigating an extreme case where the bone tissue was so deteriorated that it could be neglected. The long-term behaviour of the bone present in the augmented region is unclear, 24 so results obtained with method E are a representation of one of the worst possible cases. It is also worth noticing the similarity between approaches E (bone tissue is neglected) and B (pure porous PMMA).…”
Section: Figure 8 Distribution Of Bone Cement Volume (Relative Frequementioning
confidence: 99%
“…Consequently, one research question is whether considering the PMMA porosity for the augmented bone has a statistically important impact when predicting the optimal volume of bone cement required to achieve a specific level of bone augmentation. Furthermore, a second research task is to identify the correlation between level of osteoporosis and optimum volume of bone cement, as the latter is proven to be an important factor both for the biomechanical properties of the bone after an augmentation procedure and the long‐term behaviour of bone after augmentation . Lastly, a third research question is to quantify the sensitivity of the optimum volume of bone cement on essential design variables of the examined problem, namely the grade of porosity of PMMA, as well as the frontal and the transverse direction of the external load, resembling a fall on the greater trochanter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomechanical tests of PKP have confirmed that cement augmentation improved vertebral fracture stability, and there were no significant differences in VH restoration in in vitro studies [ 10 , 11 ]. The results of restoration of mechanical stability through VA have been also confirmed by finite element analysis (FEA), which can predict the long-term stability of a bone after cement augmentation through reliable models [ 8 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the deepening understanding of PVP surgery and the advances in biomechanical experiments, others believed that the new vertebral fractures after PVP were not caused by increased stiffness of the vertebral body. They indicated that it was the injected bone cement that caused vertebral body stiffness and slightly increased end-plate pressure-but not enough to lead to adjacent vertebral fractures [20,21]. Although the strength of the vertebral body was greater after PVP than before fracture, and the stiffness was partially restored, it was still less than that before the fracture [22].…”
Section: Discussionmentioning
confidence: 99%